2012
DOI: 10.1097/acm.0b013e31825837be
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Change Counseling Curricula for Medical Trainees

Abstract: Purpose Unhealthy behaviors contribute to half of U.S. deaths. However, physicians lack sufficient skill in counseling patients to change behaviors. Characterizing effective published curricular interventions for behavior-change counseling for medical trainees would inform educators toward improved training. Method The authors conducted a systematic literature search of studies published 1965–2011 evaluating curricula on behavior change counseling for medical trainees. Included studies described: (1) behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 66 publications
3
60
0
7
Order By: Relevance
“…22 A recent systematic review of behavioral change counseling curricula for medical learners found that successful curricula included a focus on addressing gaps in knowledge and performance in the practice environment and reinforcing change over time until the new behavior is well-established. 23 An electronic clinical tool has the potential to provide trainees with ready access to knowledge regarding assessing alcohol use at the point of care and provide instructional scaffolding for the learner by giving them guidance on how to apply newly acquired SBIRT knowledge and skills in a given patient case. These tools could take the form of clinical alerts, guided data collection tools populated during medical visits, decision-support tools and/or self-administered questionnaires for patients.…”
Section: Introductionmentioning
confidence: 99%
“…22 A recent systematic review of behavioral change counseling curricula for medical learners found that successful curricula included a focus on addressing gaps in knowledge and performance in the practice environment and reinforcing change over time until the new behavior is well-established. 23 An electronic clinical tool has the potential to provide trainees with ready access to knowledge regarding assessing alcohol use at the point of care and provide instructional scaffolding for the learner by giving them guidance on how to apply newly acquired SBIRT knowledge and skills in a given patient case. These tools could take the form of clinical alerts, guided data collection tools populated during medical visits, decision-support tools and/or self-administered questionnaires for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Podemos estar diante de uma formação que tenha um foco diferenciado na abordagem ao paciente, através de técnicas de anamnese e abordagem centrada na pessoa. [18][19] Pode haver também um foco excessivamente teórico e pouco prático, justificando a insegurança na execução dos exames, uma vez que é o treinamento prático, supervisionado, e a repetição que solidificam o conhecimento e trazem a segurança para a prática profissional. 18,[20][21] No Brasil, a formação do profissional médico tem objetivos bem definidos, estabelecidos pelas Diretrizes Curriculares para o Curso de Graduação em Medicina.…”
Section: Discussionunclassified
“…Esta TMC já foi proposta como um modelo para ser implementado a fim de integrar a formação profissional na educação médica 3 . Foi bastante encontrada, por exemplo, em uma revisão sistemática da literatura que buscou caracterizar a efetividade de intervenções curriculares para melhorar os comportamentos de estudantes de Medicina em relação ao aconselhamento de pacientes sobre comportamentos saudáveis 4 . Outro exemplo de sua utilização: na realização de ações educativas para promover práticas clínicas baseadas em evidência entre profissionais de saúde 5 .…”
Section: Leonardo Essado Riosunclassified